1993
DOI: 10.1063/1.353818
|View full text |Cite
|
Sign up to set email alerts
|

Techniques to minimize DX center deleterious effects in III-V device performance

Abstract: The properties of deep donor states (DX centers) in III-V alloys are discussed in relation to their influence on device characteristics and performance. The techniques to avoid or minimize such deleterious effects in AlGaAs-based devices are discussed, along with their physical basis, and some guidelines for improved III-V device design are established. New results about the benefits of proper donor selection, the role of In alloying, the advantage of δ doping in layers and in modulation-doped devices, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…It suggests that the As atoms can easily replace P atoms on the InGaP surface at high temperature when the sample was exposed to the As vapor during the gas-switching period. That is, the In x Ga 1Àx As y P 1Ày intermixing layer was easier to form at higher temperature growth [6][7][8][9][10][11][12]. In this work, the optimized growth temperature of the GaAs cap layer was 575 1C, because the As/P exchange on the surface was well suppressed at this temperature.…”
Section: Resultsmentioning
confidence: 98%
“…It suggests that the As atoms can easily replace P atoms on the InGaP surface at high temperature when the sample was exposed to the As vapor during the gas-switching period. That is, the In x Ga 1Àx As y P 1Ày intermixing layer was easier to form at higher temperature growth [6][7][8][9][10][11][12]. In this work, the optimized growth temperature of the GaAs cap layer was 575 1C, because the As/P exchange on the surface was well suppressed at this temperature.…”
Section: Resultsmentioning
confidence: 98%
“…Such a structure is missing for GaAs QDs 13 , 16 , 22 25 —in previous attempts, charge-stability was not demonstrated 31 , 32 . A materials issue must be addressed: the barrier material AlGaAs must be doped, yet silicon-doped AlGaAs contains DX-centres 33 , 34 which both reduce the electron concentration, causing the material to freeze out at low temperatures, and lead to complicated behaviour under illumination. Here, we resolve this issue—all doped AlGaAs layers have a low Al-concentration.…”
Section: Introductionmentioning
confidence: 99%
“…The growth interruption just before and after deposition of the silicon atoms was, in an introductory way, considered by Muñoz et al 33 They reported a reduction of the relative silicon concentration acting as the DX center by introducing a 15 s growth interruption. We used a 1 min interruption, so that it might play a role in lowering the concentration of the DX center.…”
Section: Persistent Photoconductivity Effectmentioning
confidence: 97%